2012
DOI: 10.1038/mt.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection of Transplanted Hepatocytes by Pharmacological Inhibition of Fumarylacetoacetate Hydrolase in Wild-type Mice

Abstract: Genetic fumarylacetoacetate hydrolase (Fah) deficiency is unique in that healthy gene-corrected hepatocytes have a strong growth advantage and can repopulate the diseased liver. Unfortunately, similar positive selection of gene-corrected cells is absent in most inborn errors of liver metabolism and it is difficult to reach the cell replacement index required for therapeutic benefit. Therefore, methods to transiently create a growth advantage for genetically modified hepatocytes in any genetic background would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In order to apply this system in any genetic liver disease, selection must work in animals that not deficient in FAH. We previously described a small-molecule inhibitor of FAH that was capable of inducing FAA accumulation and exerting selective pressure in vivo in mice (22, 23). In order to demonstrate that the Hpd shRNA could be used in any genetic background, neonatal wild-type C57Bl6 mice were injected with 2×10 11 vg of the promoterless F9 generide construct.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to apply this system in any genetic liver disease, selection must work in animals that not deficient in FAH. We previously described a small-molecule inhibitor of FAH that was capable of inducing FAA accumulation and exerting selective pressure in vivo in mice (22, 23). In order to demonstrate that the Hpd shRNA could be used in any genetic background, neonatal wild-type C57Bl6 mice were injected with 2×10 11 vg of the promoterless F9 generide construct.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that transplanted hepatocytes can be selected with CEHPOBA in vivo if they carry a genetic mutation in tyrosine catabolic enzyme (23). However, patients with such mutations are rare leaving the vast majority of clinically relevant metabolic liver diseases unamenable to this powerful selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with genetically-engineered deletion of the fah gene represent perhaps the first instance of a genetic disorder in which the feasibility of HTx was documented (Karnezis et al 2001); (Erker et al 2010); (Paulk et al 2012). Grompe and colleagues successfully exploited fah deficiency in the distal portion of the tyrosine metabolic pathway to provide an engraftment advantage for exogenously administered fah +/+ cells to fah -deficient mice.…”
Section: Htx For Inherited Metabolic Diseasesmentioning
confidence: 99%
“…tissue-restricted promoters); however, as these sequences are not specific to AAV vectors they will not be discussed here. Regarding AAV vector-specific enhancements for gene addition applications, a pivotal advancement was spurred by the observation that transgenic cassettes less than half the size of the AAV genome (≤2.3 kb) packaged both monomer and dimer single-strand DNA species that had the capability to form a duplex vector genome through antiparallel single strand complementarity (158, 174, 176). Shortly thereafter, two reports demonstrated that these dimer species could be intentionally induced using a plasmid containing a wild-type ITR sequence, transgenic DNA (≤2.3 kb) and a truncated ITR in which the trs is deleted and therefore, is deficient for Rep-induced resolution of the typical double-stranded AAV genome intermediate (Figure 2) (161, 162, 177).…”
Section: Adeno-associated Virus Vector Applicationsmentioning
confidence: 99%